PERANCANGAN VIDEO PROFIL WISATA ARBORETUM DENGAN PENDEKATAN ESTETIKA SINEMATIK - Edy Jogatama Purhita; Muhammad Ariq Fadillah; Ahmad Zainudin (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
This study aims to develop a cinematic video profile as a promotional medium for the Arboretum Village Tourism Park in Sampetan, Boyolali, Central Java. Using the Multimedia Development Life Cycle (MDLC) model, the research was conducted through six stages: concept, design, material collecting, assembly, testing, and distribution. Data collection involved field observation, interviews with village officials, and literature studies to ensure content accuracy. The video production utilized tools such as CapCut, Jitter.videos, and iPhone 11 to produce high-quality visuals, motion graphics, and narration. Alpha and beta testing with 50 respondents aged 17–25 years indicated positive audience perception, with an overall satisfaction score of 82.88%, demonstrating that the video is informative, visually appealing, and effective for digital promotion. The video was then distributed via YouTube and TikTok to increase visibility and attract visitors. This study concludes that a cinematic video profile is a viable and effective promotional tool for rural tourism destinations, combining aesthetic presentation with strategic digital communication.